Excellence of Trainer and Psychological Wellbeing Lead to the Higher Performance: Evidence from Chinese Basketball Players - Xiu-Ming Cheng , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Ryff’s Model of Psychological well-being has four major factors like Self-Acceptance, Personal Growth, Environmental Mastery, and Autonomy that contribute to an individual’s performance and personal growth. These factors are applied to Chinese basketball teams, the population of this study. The main objective of this study was to analyze the impact of psychological well-being on the higher performance of Chinese basketball players with the mediation of excellence of trainers. A simple random sampling technique was used for the data collection. Data was collected with the use of the e-mail survey method. Results generated from PLS_SEM revealed that psychological well-being factors like Self-Acceptance, Environmental Mastery, and Autonomy have a positive significant impact on the excellence of trainer and also on the higher performance of players except for personal growth and for the excellence of trainer is self-acceptance. An increase in the excellence of trainers also increases the performance of players in Chinese basketball teams. The excellence of trainers also does not mediate the relationship between psychological well-being factors like Self-Acceptance, Personal Growth, and Autonomy, and higher performance of players in Chinese basketball teams except environmental mastery. This study recommends that in order to increase the performance of player’s management, the team administration should focus on focus such as excellence of trainers and psychological well-being factors.